Socio-spatial change in the world heritage site Valparaíso - Hidalgo, Rodrigo; Borsdorf, Axel; San Martín, Gabriel (DIE ERDE – Journal of the Geographical Society of Berlin, 2014)
Valparaíso’s old town is one of five world heritage sites in Chile. Its districts of Puerto and Financiero on the coastal platform, together with the surrounding hills of Cerros Concepción and Alegre make up 0.9 % of the total urbanised area. The unique urban ensemble with its heritage of early industrialisation, the harbour installations and the many wooden funiculars have led UNESCO to make these districts a protected area. However, protection does not only mean conservation. Many morphological, functional and socio-spatial changes have taken place since the declaration as a heritage site. Some of them are due to the effects of natural and man-made disasters, but many are a result of the new function as a heritage site. Based on a morphological and functional analysis and a deeper look at the socio-spatial changes, the study returns contradictory results. Initial trends of gentrification can be observed, which may favour the conservation of the built environment, but weaken the social situation. A more severe degradation of the building stock has been halted; however, in many respects dilapidation has only been slowed down. The negative demographic trend has been exacerbated by the activities of ruthless developers who have bought up buildings with speculation in mind. Such activities have a long-term destructive effect on the immaterial cultural heritage, i.e. the vibrant and locally specific urban life in the old town. The main question is how the declaration as a world heritage site has influenced the social and economic fabric of the old town, and how the changes can be evaluated. This paper investigates the socio-economic changes, social transformations and other processes of change.